The J-Curve between Pakistan and the SAARC Region: Empirical Evidence from Aggregated and Commodity Level Trade Flows - Javed Iqbal; Saqib Ullah Khan; Misbah Nosheen (NUST Journal of Social Sciences and Humanities, 2021)
The present study attempts to investigate the J-curve phenomena at aggregate level as well as at commodity level between Pakistan and the SAARC (South Asian Association for Regional Cooperation) region by utilizing the trade data of 87 industries. For testing the J-curve phenomena, we rely on traditional definition (the negative coefficients at shorter lags should be followed by positive coefficients at higher lags) as well the latest definitions (short run deterioration followed by long run improvement). As far the aggregate level industries are concerned, we do not find the evidence of J-curve when we rely on traditional definition but we do find evidence of J-curve at aggregate level when we rely on latest definition of J-curve. Likewise, in case of industry level estimates, the J curve phenomena were confirmed in 13 industries considering the traditional definition. While using the new definition, the J curve has been confirmed in 14 industries. We suggest that depreciation is less effective to improve Pakistan’s trade balance as the trade shares of the industries showing J curve is very low.